Unequal development : an essay on the social formations of peripheral capitalism - "Amin , Samir" (Delhi, 1979)
The relationship between the advanced Capitalist and the Colonial and neocolonial countries is summarized. Inquiry into the processes of capitalist society throws new light on, among other things, international economic and financial relations, the role of money in economic expansion, the sources of persistent inflation, and the origins of the emerging crisis of world capitalism.
Keywords: Economic development